Guidelines for Research Proposal Writing in the Social Sciences - Bhattachan, Krishna Bahadur (Himalayan Journal of Sociology and Anthropology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> No abstract available Himalayan Journal of Sociology & Anthropology Vol.1 2004 p.99-105